Designing a knowledge assessment system for the Data structures and Algorithms course - Long, Hoang Ngoc; Thanh, Mai Trung; Nhon, Do Van (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2024)
The course of Data Structures and Algorithms is one of the fundamental and crucial subjects in the curriculum of the Information Technology field. This course serves as the foundation for understanding and applying data structures and algorithms in solving real-world and complex problems. However, teaching and learning Data Structures and Algorithms often face many challenges. Students often struggle with understanding and applying concepts, algorithms, and data structures to real-world problems. Moreover, assessing students’ knowledge and learning performance in the course also requires accuracy and objectivity. In this context, designing and implementing a system to support testing and evaluating knowledge for the Data Structures and Algorithms course becomes truly necessary. Such a system not only helps students grasp knowledge effectively but also provides opportunities for instructors to monitor students’ learning progress and provide feedback for them to improve their learning outcomes. The paper will present the design of techniques for building an application for testing and evaluating knowledge in the Data Structures and Algorithms course. This application will be a useful tool for both instructors and students, thereby enhancing the quality of teaching and learning in Information Technology-related subjects.